Breast reconstruction - Ahmad Kurnia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Breast reconstruction is such a unique procedure that might potentially be adjustedin line with time and all advances in technology and instruments (endoscopy,silicone implants, alloderm grafting). In addition, it adapts in accordance to better,more sophisticated knowledge of breast anatomy (vascularization, perforator, andinnervation), breast subunits, and systemic changes. Surgical techniques and thecurrently available list of materials might be utilized to reconstruct the breast insuch a way to yield cosmetic satisfaction. Combination and modification of thosetechniques might be adjusted to the patients’ requests without crossing over thepaths of the disease being corrected (cancer, benign tumor, infection, or otherbreast anomalies).Breast reconstruction’s prerequisite is the absence of cancer approximately 1cm from the edge of incision, adjusted by shape and size of breasts, and sizeof cancer. Several techniques might be applied to conserve and reconstruct thebreasts when the disease has been diagnosed. Oncoplasty applies all techniquesavailable to reaffirm the principles of oncology, by increasing the distance fromthe edges of cancer and proceeding with reconstruction by reduction/mastopexy(volume displacement), or adjacent/distant flaps (volume replacement). Thedisadvantage of BCS/BCT is the short distance from the edge of incision to thetumor due to the risk of post-operative breast deformity, especially when surgeryis followed by adjuvant radiation.